CHARLES BONNET SYNDROME: NEUROBIOLOGICAL INSIGHTS - Duggal, Harpreet S. (Medknow Publications, 2002)
A case of Charles Bonnet syndrome in an elderly patient with occipital lobe lesion is described. Authors have highlighted the complex interplay of various neurobiologicat factors such as cortical blindness, structural brain lesion and epileptiform brain activity in the pathophysiology of this syndrome. The impact on the clinical presentation of brain changes on aging and those following cortical blindness and peripheral visual loss is also discussed.